2015
DOI: 10.14411/fp.2015.014
|View full text |Cite
|
Sign up to set email alerts
|

Host-parasite and phylogenetic relationships of Myxobolus filamentum sp. n. (Myxozoa: Myxosporea), a parasite of Brycon orthotaenia (Characiformes: Bryconidae) in Brazil

Abstract: Myxobolus filamentum sp. n. was found infecting gill filaments of three of 39 Brycon orthotaenia Günther specimens examined (8%), which were taken from the river São Francisco in Minas Gerais state, Brazil. Plasmodia of the parasite were white and long, measuring 5 mm in lenght. Mature spores of M. filamentum sp. n. were oval from the frontal view and biconvex from the lateral view, measuring 7.5-9.7 µm (9.0 ± 0.3 µm) in length and 5.2-7.3 µm (6.2 ± 0.4 µm) in width. The polar capsules were elongated and equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…This feature has been reported for few other histozoic species, e.g. M. insignis (Azevedo et al ., 2013) and M. filamentum (Naldoni et al ., 2015), since the differentiation of peripheral projections is common to the plasmodial development of coelozoic species (Sitjà-Bobadilla and Alvarez-Pellitero, 1993; 2001; Rocha et al ., 2011). Overall, the ultrastructural study performed revealed significant unique features of the plasmodial development of M. exiguus , namely in its attachment to the mesothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This feature has been reported for few other histozoic species, e.g. M. insignis (Azevedo et al ., 2013) and M. filamentum (Naldoni et al ., 2015), since the differentiation of peripheral projections is common to the plasmodial development of coelozoic species (Sitjà-Bobadilla and Alvarez-Pellitero, 1993; 2001; Rocha et al ., 2011). Overall, the ultrastructural study performed revealed significant unique features of the plasmodial development of M. exiguus , namely in its attachment to the mesothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…parasites of other species of South America fishes [3,26,27] The comparison of M. curimatae n. sp. with Myxobolus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Bayesian posterior probability were determined running the Markov chains (two runs and four chains) for 4 × 10 6 generations, discarding the initial 1/4 of sampled trees (trees sample every 4 × 10 3 generations) as burn in fraction. Phylogenetic trees were rooted using Ceratonova shasta (Noble, 1950) as outgroup based upon previous Myxobolidae phylogenies ( ADRIANO et al, 2009;CAPODIFOGLIO et al, 2015;NALDONI et al, 2015).…”
Section: Methodsmentioning
confidence: 99%